Enhancing Financial Literacy: Education in Household Financial Management to Augment Family Welfare - Saravrof Tharkicv (Akademi Sertifikasi Profesi Internasional, 2025)
Proficient financial literacy is a crucial basis for home economic stability and enhanced family welfare. Numerous families in Indonesia continue to encounter difficulties in financial management, frequently resulting in issues such as substantial debt, insufficient savings, or inadequate preparedness for emergencies. This essay addresses the imperative of educating individuals in family financial management as a strategic initiative to enhance financial literacy. This project aims to assess the current level of financial literacy, develop participatory and pertinent educational models, evaluate the effects of educational implementation on favourable financial behaviour, and enhance family welfare indicators. The employed methodologies included questionnaire surveys, in-depth interviews, and focus group discussions (FGD) with family heads and homemakers. The findings indicate that organised and sustainable educational initiatives, focusing on budgeting, basic investment strategies, debt management, and the significance of insurance, can markedly enhance comprehension and application of financial management, which ultimately correlates positively with improved family welfare. This article aids in the development of more effective and inclusive financial literacy education policies and initiatives.